2006
DOI: 10.1089/fpd.2006.3.97
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Diversity Within Phage Types ofSalmonella entericassp.entericaSerotypes Enteritidis and Typhimurium

Abstract: The diversity among 1354 strains of Salmonella enterica subsp. enterica, serotype Enteritidis (n = 847) and Typhimurium (n = 507) isolated in Finland in 1991-2002 (n = 608) and in 2003 (n = 746) were studied. The former strains were studied retrospectively by phage typing and pulsed-field gel electrophoresis (PFGE) harmonized in the European Salm-gene project. The latter strains were studied prospectively, and the results correlated to their antimicrobial susceptibility and association with travel to popular t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…The antimicrobials tested were those included in the Enternet reference panel (42). PFGE was performed according to the Pulsenet protocol (27) using XbaI as a restriction enzyme.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antimicrobials tested were those included in the Enternet reference panel (42). PFGE was performed according to the Pulsenet protocol (27) using XbaI as a restriction enzyme.…”
Section: Methodsmentioning
confidence: 99%
“…Pulsed-field gel electrophoresis (PFGE) analysis showed that these tetraresistant strains belonged to a unique clonal group, different from the DT104 ACSSpSuT clone (13). Using the PulseNet Europe database (27), it has been possible to verify that ASSuT strains of S. Typhimurium and its monophasic variant isolated in Denmark and the United Kingdom exhibited PFGE patterns that were the same as or very closely related to those of the Italian strains, suggesting that an ASSuT clonal group was circulating in different European countries.…”
mentioning
confidence: 99%
“…Pulsed-fi eld gel electrophoresis (PFGE) was performed using PulseNet standardized protocol with few modifi cations (9). We considered any difference between 2 profi les to be suffi cient to distinguish 2 different PFGE profi les.…”
Section: The Studymentioning
confidence: 99%
“…Three prophage regions are mainly responsible for the difference, and include a 38 kb ST64B region, an 18 kb Fels-2 region and a few genes belonging to prophages ST27 and ST35 . Salmonella phage typing has become the recognized method by which epidemiologists attribute Salmonella outbreaks or epidemics to a specific strain type (Boccia et al, 2004;Lukinmaa et al, 2006;Usera et al, 1994). Within the last decade, S. Enteritidis PT4 and PT6 have been the most prevalent in Europe (Echeita et al, 2005;Gillespie et al, 2005), whereas in the USA and Canada, PT8 and PT13a are the most common types (Brown et al, 1999;White et al, 2007).…”
Section: Introductionmentioning
confidence: 99%